The effect of gender and age on postoperative pain in laparoscopic cholecystectomy: a prospective observational study - 채경린; 박상융; 홍정인; 임우재; 이승철; 정찬종 (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: Gender and age are known factors that affect postoperative pain. The purpose of this study was to investigate the effect of gender and age on postoperative pain and analgesic consumptions after laparoscopic cholecystectomy. Methods: We studied 240 adult patients (120 female patients and 120 male patients) who underwent elective 3-port laparoscopic cholecystectomy under general anesthesia. The numerical rating scale (NRS) scores were assessed before surgery, when the patient arrived in the recovery room, and at 8, 16, and 24 h after surgery. Analgesic consumptions in the recovery room and at 24 h postoperatively were evaluated. We compared the NRS scores and quantity of analgesics between the gender groups and the age groups (20–45, 46–64, and ≥ 65 years old). Results: Compared to male patients, female patients had higher NRS scores (6 [5, 7] vs. 5 [4, 6]; P = 0.001) and required a higher dose of fentanyl (0.94 ± 0.47 µg/kg vs. 0.79 ± 0.41 µg/kg; P = 0.011) in the recovery room. The younger female patients (20–45 and 46–64 years old) required a higher dose of fentanyl than those older than 65 years of age in the recovery room. Conclusions: Female patients exhibit higher NRS scores and greater consumptions of analgesics than male patients immediately postoperatively. Younger female patients require more analgesics than elderly patients in the recovery room. KCI Citation Count: 0